Immortal city - Speer, Scott, 1982- (Razorbill, 2012)
Jackson is the hottest Angel in the city, soon he'll be a full Guardian and people will pay for him to save them. Then he falls for Maddy who likes him for who he is and not for his celebrity, but a serial killer is loose.